2018
DOI: 10.3928/01913913-20170703-16
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical Structures in Human Extraocular Muscles and Their Potential Implication in the Development of Oculomotor Disorders

Abstract: The potential role of sensory feedback from human extraocular muscles has been subjected to considerable speculation in the ophthalmic literature. Extraocular muscles pull against a fairly even load and do not initiate a stretch reflex, even when the eyes are directed toward the boundaries of their respective field of action. These unique working conditions and physiological properties have led to the notion that the sensory signal arising from receptors in extraocular muscles differs from the conventional pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…2). This neuromuscular arrangement is consistent with that of other mechanoreceptors, indicative of a capacity to monitor active contraction as well as passive stretch [3,5]. Myotendinous cylinders reside in all cross-sectional regions of both the global and orbital layer of extraocular muscles.…”
Section: Tendon Receptorssupporting
confidence: 77%
See 1 more Smart Citation
“…2). This neuromuscular arrangement is consistent with that of other mechanoreceptors, indicative of a capacity to monitor active contraction as well as passive stretch [3,5]. Myotendinous cylinders reside in all cross-sectional regions of both the global and orbital layer of extraocular muscles.…”
Section: Tendon Receptorssupporting
confidence: 77%
“…In contrast, Sherrington advocated that the information about eye position is provided by muscle proprioceptors. Recent comparative and clinical studies have indicated that these concepts may not be mutually exclusive [5]. The latter concept has gained more support in recent years through clinical experiments in which somatic proprioception is found to influence a subject's registered eye position.…”
Section: The Role Of Proprioception In Oculomotor Controlmentioning
confidence: 99%
“…Paduca and Bruenech () indicated that surgical procedures performed on the extraocular muscles that interfere minimally with the proprioceptive signal provide a better postoperative result. Thus, detailed knowledge of the extraocular muscles' innervation pattern may be of utmost clinical importance, especially in neuroophthalmology, as it may help to better understand the nuances of selected physiological reflexes (such as, the vestibulo‐ocular reflex or ocular counter‐rolling reflex) and of eye movement control in normal and pathological conditions (Goldberg et al, , ; Demer et al, ; Oh et al, ; Guthrie, ; Peng et al, ; Clark and Demer, ; Demer and Clark, ; Paduca and Bruenech, ). Therefore, this study's purpose was to examine the lateral rectus muscle's detailed pattern of innervation, including the distribution of the abducens nerve's intramuscular subbranches.…”
Section: Introductionmentioning
confidence: 99%
“…As there are other variables that can influence the surgery outcome, such as the type of surgery (sensory status of the patient, bilateral recession of the rectus muscle vs unilateral recession-resection), high refractive errors, oblique muscle dysfunction or pattern of strabismus, the chosen anatomical features and surgical techniques, as well as the surgeon's experience, techniques such as differences in muscle exposure, suturing application, style of attachment, surgical volume measurement and, even proprioception disroption during strabismus surgery. [42][43][44][45][46][47] Identifying these factors can improve the surgery outcome and identify a group with long-term stable compliance. In addition, these models needs to be validated using an independent sample in the following studies.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%